2018
DOI: 10.24321/2349.2880.201728
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Aggression among School Adolescents in Karnataka, India

Abstract: Introduction: Adolescents are placed in critical stage of human development when they are stepping from childhood to adulthood. Worldwide, it is seen that aggression is one of the most common features in this group. Aims and Objectives:(1) To identify aggression among school-going adolescents and (2) To assess different sociodemographic characteristics associated with aggression among these students Methodology: A cross-sectional descriptive study was conducted in one of the private schools in Karnataka from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Delinquent behaviour is found to be high among inmates of Juvenile Homes. This finding is consistent with other studies, 18,20 and is expected as children who conflict with the law and those who need care and protection due to neglect or maltreatment are placed in juvenile homes. Studies reported an association between maltreatment and the ability to regulate emotions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Delinquent behaviour is found to be high among inmates of Juvenile Homes. This finding is consistent with other studies, 18,20 and is expected as children who conflict with the law and those who need care and protection due to neglect or maltreatment are placed in juvenile homes. Studies reported an association between maltreatment and the ability to regulate emotions.…”
Section: Discussionsupporting
confidence: 92%
“…19 Delinquent behaviour, aggression, and substance use were reported in studies among school children also. [20][21][22] The importance of emotion regulatory strategies in the treatment of delinquent youth was also reported [23]. The present study aims to determine whether a child's emotional intelligence has any bearing on his delinquent behaviour.…”
Section: Introductionmentioning
confidence: 90%
“…In a study conducted at Karnataka, India more aggression is seen among boys whose mothers were less educated as compared to girls. That means educated mothers can help their children in reducing or managing their anger (Kumari et al, 2017 (Björling and Singh 2017). Keeping these pieces of literature in view, one question comes to our mind that how these negative angers can be controlled and is there any scientific evidence available in the literature.…”
Section: Anger and Adolescentsmentioning
confidence: 99%
“…It is very necessary to be aware of gender and age differences during adolescence as well as anger and aggression problem during this stage. To understand these things, intervention programs should be started early in life so that they can help to reduce aggression among adolescents (Kumari et al, 2017). However, in the lack of time and to develop policy especially for the adolescent government must conduct more research and conduct regular classes on health issues at school and college level with demonstration of good practices.…”
Section: Suggestions:-mentioning
confidence: 99%
“…It is also a predictor of a broad spectrum of adult adjustment problems (Coie & Dodge, 1998). A study by Kumari et al (2017) studied the cognitive component of aggressive tendencies among Indian adolescents and found that one third of the adolescents who participated in their study had beliefs supporting aggression. It is noteworthy that 21% (about 243 million) of the Indian population comprises adolescents (United Nations Children’s Fund [UNICEF], 2011), forming a significant demographic and economic force.…”
mentioning
confidence: 99%